Current Outlook of Livestock Industry in Malaysia and Ways Towards Sustainability - Zayadi, Rabiatul Adawiyah (Journal of Sustainable Natural Resources, 2021)
This paper reviews the current status of livestock industry in Malaysia and the measures taken to direct this industry towards sustainability. The statistics related to the number of animals and farms, self-sufficiency ratio, and consumption of livestock products are presented. The largest population of livestock in Malaysia goes to non-ruminant where chicken dominates by 95.9%. However, the largest percentage of registered livestock farms in West Malaysia is dominated by ruminant farmers of which 56.3% are beef cattle farms. The meat consumption in Malaysia is inclined towards white meat where poultry meat has self-sufficiency ratio of over 100% for the past five years. The manure excreted from the livestock in Malaysia is estimated to be 17.745 million tons for the year 2020 which is largely contributed by chicken, followed by cattle. The current practices and policies adopted to emphasize sustainability in this industry are also reviewed. Current policies in Malaysia that are related to livestock industry adopt sustainable practices which is important to expand the livestock industry without harming the environment.